The slowest burn : a novel - Chamberlain, Sarah, 1987- (St. Martin's Griffin, 2024)
""A five course feast of longing, banter, gourmet cooking, heaps of spice, and a cherry on top happily ever after. I devoured this fake dating, celebrity chef romance." -Erin La Rosa, author of Plot Twist and For Butter or Worse Business or Pleasure meets Evvie Drake Starts Over in this delicious opposites-attract romance from debut author Sarah Chamberlain. Sometimes the perfect recipe just needs a little extra heat. Ellie Wasserman's life is neat and tidy, and that's exactly how she wants it. Really. A top ghostwriter for celebrity cookbooks, she was widowed three years ago and has no interest in taking chances-not on writing her own cookbook, not on telling her still-grieving in-laws she wants to move out, and certainly not on dating, which is about as intimidating as a recipe with fifty steps. Kieran O'Neill isn't known for being organized. An up-and-coming chef who scored big on a reality television competition, he's been the guy who cracks jokes and makes messes-something his chilly family has never let him forget. The only place he feels truly capable is at the stove. But when he's paired with an uptight ghostwriter with cool blue eyes and distracting curves to write his debut cookbook, she shreds his class clown act like a paring knife cuts an orange peel. As Ellie and Kieran are forced to work closely together in a hot kitchen for weeks on end, their sharp edges and harsh judgments slowly soften and sweeten into a wildly delicious attraction. Long, steamy days turn into even steamier nights, but they have to face their painful pasts to know if this tender new love can transform into something lasting. "A romance as sharp as it is sweet. Fans of Emily Henry will devour this delectable story of love lost and found." -Cecilia Rabess"--